(untitled) (The International Journal of Educational Sciences and Arts, 2024)
The study aimed to analyze the position of primary school teachers on the use of the flipped classroom strategy in education, determine the type of relationship between employing the flipped classroom strategy and improving learning outcomes, and explore the impact of using the flipped classroom strategy on improving learning outcomes for sixth grade primary school students. In light of the nature of the study and its objectives, the descriptive approach was used with its analytical and survey methods that are based on collecting data and answering its questions and analyzing them. The study community was the sixth grade primary school teachers in the Al-Fadhila Office in Jeddah Education. The study sample consisted of (121) male and female teachers, (49) male and (72) female teachers. An electronic questionnaire consisting of three axes was used to collect data, (5) for primary data, (17) paragraphs for the first axis, which is employing the flipped classroom strategy in the educational process, (7) paragraphs for the second axis related to employing the flipped classroom strategy in improving learning outcomes for sixth grade primary school students. The Most Important Results of the Study Were: - Conducting electronic tests for students and evaluating them based on them is very appropriate in the flipped classroom strategy environment, such as Nafis tests and others. -The flipped classroom strategy improves students’ memorization and comprehension skills within the educational outcomes measured by the curricula in the primary stage. - The importance of the role of parents in helping and guiding their children by providing tools and technology that help them achieve in light of the flipped classroom strategy at home. - The necessity of training the teacher to use the applications available on the Internet that allow students to interact with him during the explanation in the flipped classroom strategy environment and to employ them well. - The flipped classroom strategy contributes to developing students’ academic achievement skills by viewing a larger number of sources that enrich the student’s educational material. The Most Important Recommendations of the Study Were: - That school administrations encourage teachers to continue to employ the flipped classroom strategy more. - The necessity of the teacher’s interest in updating and developing his knowledge about active teaching strategies in the educational process and how to use them with students in the classroom.